Women's Mental Health in the Time of Covid-19 Pandemic - Thibaut, Florence; van Wijngaarden-Cremers, Patricia J. M. (Frontiers in Global Women's Health, 2020)
Even if the fatality rate has been twice higher for men than for women, the Covid-19 pandemic has affected women more than men, both as frontline workers and at home. The aim of our article was to analyze the differences observed in mental health and violence between men and women in the COVID outbreak. For this purpose, we have used all papers available in PubMed between January and July 2020 as well as data from non-governmental associations. We have thus successively analyzed the situation of pregnancy during the pandemic; the specific psychological and psychiatric risks faced by women both as patients and as workers in the health sector, the increased risk of violence against women at home and at workplace and, finally the risk run by children within their families. In conclusion, research on the subject of mental health issues during the Covid-19 pandemic is still scarce, especially in women. We hope that this pandemic will help to recognize the major role of women at home and at the workplace.